Tradisi Pesantren Dipondok Pesantren Al Madaniyah Kecamatan Jaro Kabupaten Tabalong - Rabiyatul Fauziah; Rabi’ah Rabi’ah; Akhmad Mawardi Syahid (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2023)
This study proposes about the traditions of the Islamic boarding schools at the Al-Madaniyah Islamic Boarding School, Jaro sub-district, Tabalong Regency. This thesis research is A field research using qualitative methods, the subjects of this research are ustadz, ustadzah, mukhaddimah, young women and female students at the Jaro Al-Madaniyah Islamic Boarding School, and the object of this research is the Islamic Boarding School Tradition at the Al-Madaniyah Putri Islamic Boarding School, Jaro District, Tabalong. Data collection techniques using interviews, observation, and documentation. After the necessary data is obtained and collected, it is then processed using reduction techniques, data display and data verification, then analyzed using a qualitative descriptive method. Based on the results of this study it can be concluded that the Islamic Boarding School Traditions at the Al-Madaniyah Putri Islamic Boarding School, Jaro District, Tabalong Regency include, a description of the Kyai at the Al-Madaniyah Putri Islamic Boarding School that the kyai is an inspirational and motivating person for students and ustadz, and the kyai is role model for students. The description of the Santriwati at the Al Madaniyah Putri Islamic Boarding School that the santriwati has differences with a student makes the santri superior in the field of religion than other students. The description of activities at the Al-Madaniyah Putri Islamic Boarding School Mosque that activities in the mosque are the most important places at Jaro Al-Madaniyah Islamic Boarding School. The description of activities at the Al-Madaniyah Putri Islamic Boarding School Dormitory that the dormitory is a place for female students to gather in carrying out all activities and a dormitory is a place to build togetherness among fellow students through Ukhuwah Islamiyah. The description of the Kitab Kuning curriculum at Al-Madaniyah Putri Islamic Boarding School that the Kitab kuning curriculum used is traditional and modern as well as the method used is not only listening but being able to write allegories, quotes from the Kyai.